Potret Insan Unggul Perspektif Al-Qur’an (Antara Postulat Al-Qur’an dan Harapan Pendidikan Islam) - Wahyudin Wahyudin; Nurlaelah Sultan (Education and Learning Journal, 2023)
Producing quality and superior human beings is always an interesting matter to study, so it often becomes a topic of discussion in various discussion forums and scientific meetings. To give birth to superior human beings, it cannot be separated from talking about human nature itself. Understanding the nature, nature and character of human beings is a strategic key in the effort to build "human beings" of plenary people, as well as being the basic capital of understanding in initiating Islamic humanist education. As a hudan, the Qur'an has provided clear and ideal postulates about humans by providing a clear picture of the nature, nature and character of humans by conveying information that humans are creatures who have extraordinary innate potential (nature) that can be developed. and empowered through education, and this can be done if we understand the concept of human insaniyah and basyariyah. In fact, the Qur'an has described the characteristics of a superior and qualified human being by providing a very well-established conceptual reference through various verses of the Koran which talk about humans with all their unifications, for example the description of humans as "hanief", humans who are inclined to truth. and noble values, and giving mandate to humans as khalifatullah fi al-ardh is clear evidence that humans are special creatures and this is the main task of the world of Islamic education to realize this by giving birth from the "womb" of superior human Islamic educational institutions and quality.